Global Ice Forces and Ship Response to Ice. Analysis of Ice Ramming Forces - Chen, Yung-Kuang; Tunik, Alfred L.; Chen, Albert P-Y (1990)
During September and October of 1985 the Polar Sea conducted ice impact tests on heavily ridged ice features in the Alaskan portion of the Beaufort Sea. Bending Strain gage measurements were used to estimate the longitude bending moment distribution of the POLAR SEA during impacts with ice pressure ridges. Compressive strains along the stem and ship acceleration and velocity measurements were also recorded. This paper describes the methodology for determining the global ice impact force from the measurements and presents the results of these tests. A comparison of the results with other available data is also presented. Hull strain, and impact force time histories are presented along with the longitudinal bending and shear distributions during ice impact events. The results indicate that the method used in estimating the impact force provided an excellent understanding of ship-ice interaction. This supplement to the main report (Global Ice Forces and Ship Response to Ice, SSC- 341 ADA231539) contains a discussion of a finite element model that was developed to predict ice ramming forces and includes a comparison of the model's results with selected ramming events.